METODE PENDEKATAN STUDI HADIS TEMATIK DENGAN GROUNDED THEORY ANSELM STRAUSS DAN BARNEY GLASER - Ramadhan, Muhammad; Alif, Muhammad (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This study examines how Anselm Strauss and Barney Glaser’s Grounded Theory technique and the thematic hadith study (mawḍū‘ī) method can be combined. The purpose of this study is to use inductive and methodical methodologies to develop substantive theory based on hadith. While Grounded Theory provides a methodical approach to qualitative data analysis that includes open coding, axial coding, and selective coding, thematic hadith study allows for the categorization of hadith according to specific themes. This study examines the hadiths of the Prophet Muhammad SAW with a focus on religion and social concerns using qualitative methodology and textual analysis methods. The Grounded Theory method is used to evaluate primary data sources, namely original hadith books such as Sahih al-Bukhari and Sahih Muslim. Documentation is used for data collection methods, and the open to selective coding stage is used for data analysis to identify categories and relationships between ideas. The in-depth analysis of this study reveals that religious values ​​in Islam include important social components defined by empathy, accountability, and solidarity. The findings of this study indicate that this method produces ideas about Islamic Social Religion, namely ideas about religion expressed through empathy. These results show how hadith can be used as a source of contextual and useful social religious ideas when the analysis of themes and basic theories are combined. This study encourages an interdisciplinary approach that is more relevant to the current social reality of Muslims and offers a methodological contribution to current hadith studies.